Neurologists and Clinical Informatics: Realizing the Potential of Digital Medicine - Wu, Allan D.; Kummer, Benjamin R. (Seminars in Neurology, 2025)
Clinical informatics (CI) is an emerging field within biomedical informatics that sits at the intersection of clinical care, health systems, and health information technology (IT). CI emphasizes how individuals (neurologists, patients, staff) interact with health IT (HIT), with a focus on designing systems that support optimal neurologic care. As neurology becomes more complex—expanding diagnostics, treatments, and subspecialties—there is a growing need for usable, efficient electronic health record systems that enhance, rather than burden, care delivery. This paper reviews roles CI neurologists can play, as translators, architects, advocates, and leaders across clinical, operational, and strategic domains. We highlight examples where CI expertise addresses challenges in neurology, including access to care, documentation burden, burnout, quality improvement, patient engagement, artificial intelligence, research registries, and precision health. With projected workforce shortages in neurology and CI, neurologists with CI expertise will ensure that HIT will effectively support high-quality neurologist-led care.
Keywords: clinical informatics; electronic health records; neurology; health information technology; digital medicine